2019
DOI: 10.20452/pamw.15082
|View full text |Cite
|
Sign up to set email alerts
|

Congenital structural and functional fibrinogen disorders: a primer for internists

Abstract: Congenital qualitative and quantitative fibrinogen disorders represent heterogeneous rare abnormalities caused by mutations in one of the 3 genes encoding individual fibrinogen polypeptide chains, located on chromosome 4q28. It is estimated that congenital fibrinogen disorder accounts for 8% of rare coagulation factor deficiencies. Most of congenital fibrinogen disorders are suspected in individuals with bleeding tendency or coincidentally discovered, for instance prior to surgery. Fibrinogen disorders could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Second, several fibrinolysis and coagulation proteins which are involved in thrombin generation, fibrin formation, and fibrinolysis, including prothrombin, antiplasmin, plasminogen, and platelet-derived proteins, have not been evaluated [22,29,32]. Genetic modifiers of fibrin clot properties have not been assessed by us [33]. However, the mechanisms underlying the observed differences between two groups of patients were beyond the scope of the current research.…”
Section: Discussionmentioning
confidence: 95%
“…Second, several fibrinolysis and coagulation proteins which are involved in thrombin generation, fibrin formation, and fibrinolysis, including prothrombin, antiplasmin, plasminogen, and platelet-derived proteins, have not been evaluated [22,29,32]. Genetic modifiers of fibrin clot properties have not been assessed by us [33]. However, the mechanisms underlying the observed differences between two groups of patients were beyond the scope of the current research.…”
Section: Discussionmentioning
confidence: 95%
“…The latter genotype was found in 5 of 12 patients with free flap thrombosis, as shown in Table 4. Undas and Casini (2019) previously reported that patients with hereditary dysfibrinogenemia are highly heterogeneous in clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of plasminogen activator inhibitor type 1 (PAI-1) have been identified both in the blood of coronary artery disease (CAD) patients and within unstable plaques [28]. Some genetically determined fibrinogen disorders, dysfibrinogenemias, have also been linked to atherosclerotic vascular disease and its thromboembolic manifestations, supporting the view that alterations to fibrin structure and function might be of greater importance than the fibrinogen concentration itself [29][30][31].…”
Section: Blood Coagulation and Fibrin Formation In Atherosclerosismentioning
confidence: 99%